The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1139/cjm-2018-0251
|View full text |Cite
|
Sign up to set email alerts
|

Sand bedding as a reservoir for Lactococcus garvieae dissemination in dairy farms

Abstract: Lactococcus garvieae is now recognized as a species with clinical significance for human and veterinary medicine. The aim of this study was to evaluate the presence of this pathogen in sand bedding and milk samples. Two farms in Minnesota with problems of clinical and subclinical mastitis due to streptococci-like organisms were selected. Twenty-four Lactococcus garvieae isolates from sand bedding and 18 isolates from quarter milk were comparatively studied using a genotypic approach. RAPD (random amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This finding is consistent with recent case reports of Lactococcus spp. outbreaks occurring in herds using inorganic bedding (Werner et al, 2014;Rodrigues et al, 2016;Eraclio et al, 2019).…”
Section: Bedding Type Choicementioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with recent case reports of Lactococcus spp. outbreaks occurring in herds using inorganic bedding (Werner et al, 2014;Rodrigues et al, 2016;Eraclio et al, 2019).…”
Section: Bedding Type Choicementioning
confidence: 99%
“…The positive association between SSLO counts and odds of SSLO-IMI is consistent with conventional understanding of these pathogens. Like NAS, molecular methods have implicated bedding material and other environmental sources as possible reservoirs for these pathogens (Eraclio et al, 2019). However, other studies have shown that some SSLO (especially Streptococcus uberis) can exhibit host adaptation and thus establish new IMI from intramammary reservoirs (Davies et al, 2016).…”
Section: Bedding Bacteria Count Was Associated With Intramammary Infementioning
confidence: 99%
See 1 more Smart Citation
“…Bedding can be an important factor in teat skin contamination or colonization and IMI-associated strains of some bacterial species have been identified in bedding material (Eraclio et al, 2019). Bedding bacterial counts are positively associated with odds of an IMI (Rowe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated a correlation between bedding bacterial counts (BBC) and the counts of bacteria on the teat apex of cows using that bedding, suggesting that bedding may be a substantial source of bacteria colonizing the teat epithelium [ 8 , 20 23 ]. Molecular epidemiologic studies have identified IMI-causing strains of bacteria in bedding material, suggesting that bedding can act as a reservoir for some pathogens [ 24 , 25 ]. Aerobic culture of bedding to determine BBC has been used to estimate bedding-associated mastitis risk [ 5 , 6 ].…”
Section: B Ackgroundmentioning
confidence: 99%